Acculturation of Islamic and Javanese Culture in the Mujahadah Sinar Surya Demak: A Study of Living Qur'an and Hadith: (Akulturasi Budaya Jawa dan Islam pada Mujahadah Sinar Surya Demak: Studi Living Qur’an dan Hadis) - Masayu Mutia Umar; Dewi Sholihatun; Muchlisatun Nisa; Dani Daffa Priyolaksono (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to identify and analyze the forms of cultural and religious acculturation in the implementation of Mujahadah Sinar Surya by the Majelis Sekaran Jati in Demak Regency, and to examine this phenomenon from the perspective of the living Qur'an and Hadith. A socio-anthropological approach was employed to explore the social and cultural aspects of this study. The research used a qualitative descriptive-analytical method to describe the phenomenon and interpret the research data. Observational techniques and interviews were used to collect primary data, while documentation was used as supporting data. The results show that the implementation of Sinar Surya Mujahadah not only reflects Islamic teachings but also involves local cultural values. Elements of acculturation are evident in Javanese cultural symbols such as the wayang gunungan, the Javanese calendar for scheduling activities, and the use of batik and blangkon by the congregation. This demonstrates that Islam can adapt to local culture without leaving the essence of its teachings. This study contributes to understanding the integration of religion and culture as a harmonious local identity.